PROYECTO DE FACTIBILIDAD PARA LA CREACION DE UNA PLANTA DE PROCESAMIENTO DE PRODUCTOS LACTEOS EN LA PARROQUIA VALLADOLID Y SU COMERCIALIZACION EN EL CANTON PALANDA, PROVINCIA DE ZAMORA CHINCHIPE - Capa Armijos, Edgar oswaldo (2016)
The present research on "Feasibility Project for the Creation of a dairy processing plant in Valladolid parish" was held in the city Palanda, Zamora Chinchipe whose objectives were. Conduct a market survey to determine the level of supply and demand in the city Palanda. Conduct a technical study to determine the requirements in terms of size, location and project engineering. Budgeting, determining the amount of investment and funding sources. Evaluate the project by the various indicators such as NPV, IRR, and PRC, RB / C and sensitivity analysis To meet this objective methods, techniques and procedures which allowed research to develop and test the veracity of the project were used, methods used were: inductive method, deductive method. In the market study the application of consumer surveys took place in the city Palanda to determine demand and interviews to determine the offer marketers and producers to determine the production potential in the sector. The technical study size requirements are determined, the macro and micro location of the plant was also determined and project engineering In addition, this paper consists of an organizational structure, as well as their respective legal basis, organizational structure and manuals relating to the company functions. The total amount of the investment amounts to $ 10 a term 112.3743,32 dollars, the same $ 57,000.00 which represents 51% of the investment will 5 be financed by a loan from BNF with an interest rate of 11% years, in addition it will feature an internal capital of $ 55,374.32 the same to be financed by the partners of the company and which amounts to 49% of the investment. The financial evaluation determined that the project is feasible, however, also revealed that it is extremely sensitive to changes in income and expenses Finally, they do have the respective conclusions and recommendations accompanied by the bibliography consulted with their respective annexes